2013
DOI: 10.2478/s11535-013-0190-5
|View full text |Cite
|
Sign up to set email alerts
|

Movements and flight morphology in the endangered Large Blue butterflies

Abstract: Movements and flight morphology of the endangered Large Blue butterflies Phengaris teleius and P. nausithous in southern Poland were studied with mark-release-recapture surveys and GIS analyses. Most individuals moved relatively small distances (<40 metres) within their habitat patches. Distances covered by both species were positively related to season progression and wing length, and negatively related to body mass. P. teleius movement distances slightly exceeded those of P. nausithous. In addition, femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Specifically, it has been found that mobility is negatively affected by body mass, but positively by thorax width and wing length (Berwaerts et al 2002;Skórka et al 2013). The results of the present study generally confirm the above patterns, although we found that wing loading index is more useful as a factor explaining the dryad mobility.…”
Section: Discussionsupporting
confidence: 85%
“…Specifically, it has been found that mobility is negatively affected by body mass, but positively by thorax width and wing length (Berwaerts et al 2002;Skórka et al 2013). The results of the present study generally confirm the above patterns, although we found that wing loading index is more useful as a factor explaining the dryad mobility.…”
Section: Discussionsupporting
confidence: 85%
“…wing span or thorax width), which is often used as a proxy for mobility (Nieminen et al ., 1999; Greenleaf et al ., 2007; Öckinger et al ., 2010; Kuussaari et al ., 2014). Numerous studies suggest that larger individuals tend to be able to cover longer flight distances (Nieminen et al ., 1999; Berwaerts et al ., 2002; Kalarus et al ., 2013; Skórka et al ., 2013a), and body size could also influence population densities, and the other way around. High population densities during the larval stage could lead to reduced larval development time, thereby decreasing the risk of resource depletion before metamorphosis.…”
Section: Introductionmentioning
confidence: 99%
“…The multi‐causality of dispersal has been fully appreciated in recent years (reviewed by Matthysen ), suggesting that complex interactions between several factors influence the dispersal process (Skórka et al. , Legrand et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Third, we assessed individual variation in several morphological parameters (e.g., thorax–abdomen ratio, wing loading, and fat content) that may be associated with movement ability (Skórka et al. , Legrand et al. ).…”
Section: Introductionmentioning
confidence: 99%